2015
DOI: 10.1123/pes.2014-0061
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Home Environment and After-School Physical Activity and Sedentary Time Among 6th Grade Children

Abstract: This study examined associations of various elements of the home environment with after-school physical activity and sedentary time in 671 sixth-grade children (Mage = 11.49 ± 0.5 years). Children’s after-school total physical activity (TPA), moderate-to-vigorous physical activity (MVPA) and sedentary time were measured by accelerometry. Parents completed surveys assessing elements of the home social and physical environment. Mixed-model regression analyses were used to examine the associations between each el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
1
25
0
3
Order By: Relevance
“…Our findings are also in line with previous studies which show that characteristics of the physical home environment are associated with children's MVPA and ST levels ( Lau et al, 2015 ). We show that the proportion of MVPA in children increased significantly with each additional piece of PA equipment reported in the household.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in line with previous studies which show that characteristics of the physical home environment are associated with children's MVPA and ST levels ( Lau et al, 2015 ). We show that the proportion of MVPA in children increased significantly with each additional piece of PA equipment reported in the household.…”
Section: Discussionsupporting
confidence: 93%
“…The family environment serves a fundamental role in the establishment of dietary, physical activity, and other weight-related behaviors among youth. While a number of studies have explored how diet- or activity-related parental behaviors, including feeding practices [ 13 15 ], modeling [ 16 , 17 ] and providing support for health behaviors [ 18 , 19 ], as well as general parenting style [ 20 22 ] may influence adolescent weight and related behaviors, few studies have explored how other factors in the general family environment, such as family functioning or quality of parent-adolescent relationship, may influence these outcomes. Family systems theory asserts that an individual’s behaviors must be understood within the family context [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research has shown that adolescents with eating disorders report higher levels of family dysfunction [ 26 , 27 ], only a small number of studies have examined whether family functioning is associated with adolescent obesity [ 28 31 ]. Results of this existing research are inconsistent; two studies found no significant association between family functioning [ 30 , 31 ] and adolescent weight status and two found that higher family dysfunction was associated with higher weight status among youth [ 18 , 19 ]. The majority of research exploring the association between family functioning and obesity risk has included small, convenience samples [ 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other factors such as parental support, the involvement of parents and friends in sports activities, and socioeconomic status may influence the practice of physical activity of adolescents in the school shift 27,29,30 .…”
Section: Discussionmentioning
confidence: 99%